Effects of an online mindfulness-based cognitive therapy for caregivers of children with allergic rhinitis - Yan, Xixi; Xiong, Zhongwei; Sun, Huimin; Li, Jieli; Gao, Yadong; Zhang, Jinjin; Ding, Xiaomin (Frontiers in Psychology, 2024)
The incidence of allergic rhinitis in children is high across the world, as well as in China. Allergic rhinitis in children has serious impact on physical and mental health of the children. At the same time, the caregivers of allergic rhinitis children have heavy burden of care, and their mental problems are severe. It is necessary to implement timely psychological intervention for the caregivers of allergic rhinitis children. Mindfulness-Based Cognitive Therapy (MBCT) is a safe and effective psychological therapy, and the effect of online intervention can be comparable to the traditional face-to-face intervention programme. This study focused on the mental health status in the main caregivers of children with allergic rhinitis, and conducted a modified online MBCT intervention on the caregivers, in order to improve their adverse mental state, meanwhile, improve the quality of care they provide. The results show that online MBCT intervention is applicable to the main caregivers of children with allergic rhinitis, and can effectively reduce caregiver burden, relieve anxiety and depression, and improve the level of mindfulness in the caregivers.Allergic rhinitis in children is a common chronic disease in childhood and adolescence in China, and it affects about 14% of children worldwide (Li et al., 2011; Aït Khaled et al., 2009). Allergic rhinitis 字体: (默认)Times New Roman 设置格式[Xixi Yan]: 字体: (默认) Times New Roman, (中 文)宋体, 小四, 图案: 清除(自动设置), (中文)中文(简 体